Resting state functional connectivity responses post-mild traumatic brain injury: a systematic review. (19th September 2021) - Morelli, Nathan; Johnson, Nathan F.; Kaiser, Kimberly; Andreatta, Richard D.; Heebner, Nicholas R.; Hoch, Matthew C.
ABSTRACT: Mild traumatic brain injuries (mTBI) are associated with functional network connectivity alterations throughout recovery. Yet, little is known about the adaptive or maladaptive nature of post-mTBI connectivity and which networks are predisposed to altered function and adaptation. The objective of this review was to determine functional connectivity changes post-mTBI and to determine the adaptive or maladaptive nature of connectivity through direct comparisons of connectivity and behavioral data. Literature was systematically searched and appraised for methodological quality. A total of 16 articles were included for review. There was conflicting evidence of post-mTBI connectivity responses as decreased connectivity was noted in 4 articles, 6 articles reported increased connectivity, 5 reported a mixture of increased and decreased connectivity, while 1 found no differences in connectivity. Supporting evidence for adaptive post-mTBI increases in connectivity were found, particularly in the frontoparietal, cerebellar, and default mode networks. Although initial results are promising, continued longitudinal research that systematically controls for confounding variables and that standardizes methodologies is warranted to adequately understand the neurophysiological recovery trajectory of mTBI.